ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DAN DISPOSISI MATEMATIKA SISWA PADA MATERI SPLDV - Siti Nur Aliah; Suci Sukmawati; Wahyu Hidayat; Euis Eti Rohaeti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
In this study the authors analyzed the difficulties of students in the process of mathematical problem solving skills and to determine the disposition of students on each item statement. Based on the analysis, for SPLDV material the mistakes made by students in working on mathematical problem solving problems lie in the indicators of understanding the problem only reaching 34% and the average percentage of students' mathematical problem solving abilities in the category instruments. The instrument used is a question that has been tested for reliability, validity , different power and difficulty indexes have also been validated by expert validators. The mathematical disposition of junior high school students is only 65% of the SPLDV material. Indicators of student interest and reflection in learning get the smallest percentage, which is 61%, thus influencing other indicators. The research method uses descriptive qualitative analysis to find out in depth the achievement of indicators of problem solving abilities and mathematical dispositions on each item statement. Based on the results of the overall research that the achievement of indicators of problem solving abilities and student dispositions is high.